Rheological properties and emulsion stability performance of invert emulsion drilling fluid using emulsifier derived from waste cooking oil - Arina Sauki; Zahira Hanim Zainal Abidin; Nur Arifah A’la Mohd Yazid; Nurul Aimi Ghazali; Nik Khairul Irfan Nik Ab. Lah; Wan Zairani Wan Bakar (Chemical Engineering Transactions, 2024)
This study investigates the rheological properties and emulsion stability of invert emulsion drilling fluids using emulsifiers derived from waste cooking oil (FA-WCO) compared to commercial emulsifiers (CPE) and stearic acid (FA-SA). The objective is to develop an environmentally friendly and cost-effective emulsifier for high-pressure, high-temperature (HPHT) drilling conditions. The research involved preparing oil-based mud (OBM) samples at varying oil-water ratios (70/30, 80/20, 90/10) and temperatures (250°F and 400°F) and analyzing their performance using different emulsifiers. The findings revealed that the FA-WCO emulsifier exhibited comparable rheological behavior and emulsion stability to the CPE, with an optimal performance at an 80/20 oil-water ratio and 250°F. The plastic viscosity and yield point of FA-WCO were similar to those of CPE, and the emulsion stability was also closely matched. Stearic acid (FA-SA) showed higher plastic viscosity, yield point and gel strength but struggled with thermal stability at temperature more than 250°F. The study concludes that emulsifiers derived from waste cooking oil offer a sustainable and effective alternative for drilling operations, reducing environmental impact and promoting the recycling of waste materials. The results recommend the adoption of FA-WCO as a viable emulsifier in the oil and gas industry, particularly for HPHT drilling applications.